Mathematical and Computational Models of Cell Cycle in Higher Eukaryotes - Krivdic, Alma (Springer-Verlag Singapore Pte Ltd, 2017)
The cell cycle is an ordered sequence of coordinated biological processes that enable cells to grow and divide, to check for certain abnormalities whenever it is appropriate, to regulate the different stages of growth and division in the predefined order, and to respond to DNA damage and other dysfunctions by arresting progression through the cell cycle so that to allow the regulators to repair DNA damage and recover from dysfunction before DNA is completely replicated. Mathematical and computational modeling and simulation is a well-known approach to explore biological systems. The main idea behind this approach is to create the closest approximation of a biological system based on wet lab results, and predict its dynamic behavior through measuring the amounts of biological components. Mathematical and computational approaches implemented to cell cycle regulation have the following benefits. Firstly, it makes possible to provide a detailed qualitative and quantitative structure of the biological system describing the cell cycle regulation. Secondly, modeling allows us to conjecture a hypothesis regarding the biological system and then check consistency of the hypothesis to desired deep by extrapolating the parameters involved into the model.
International Conference on Medical and Biological Engineering in Bosnia and Herzegovina (CMBEBIH) -- MAR 16-18, 2017 -- Sarajevo, BOSNIA & HERCEG
Keywords: cell cycle; mathematical model; computational model; Petri nets